Sacralizing Statecraft: A Bruce Lincolnian Analysis of Religious Conflict in Iran-israel - Baidhowi, Ridho; S. Truna, Dody; Rosyad, Rifki (Candidate: Jurnal Sains Politik, 2024)
This study investigates the Iran–Israel conflict through the theoretical lens of Bruce Lincoln’s conception of religion as an arena of conflict. It explores how religious discourse is instrumentalized by both states to construct legitimacy, sanctify geopolitical agendas, and mobilize national identity. Using a qualitative, thematic approach grounded in critical discourse analysis, the research identifies five key dimensions of religious performance: martyrdom, sacred geography, demonology, ritual mobilization, and authoritative speech. Drawing on primary sources such as state speeches, constitutional texts, public rituals, and official media from 2006 to 2024, the study illustrates how both Iran and Israel produce competing theopolitical narratives. These narratives embed political goals within frameworks of divine mandate, portraying the conflict not only as territorial or ideological but as a sacred struggle. The findings suggest that religious language in both contexts functions simultaneously as a moral compass, a political strategy, and a boundary marker that delegitimizes the ‘other.’ Through Bruce Lincoln’s theory, this research highlights how ritual, myth, and religious authority become mechanisms of statecraft in deeply divided societies. Understanding this dynamic is essential for any serious attempt at conflict resolution in the region.